Ovocidal action of glutaraldehyde and benzalkonium chloride mixture on Aonchotheca bovis (Nematoda, Capillariidae) embryogenesis - Melnychuk, V. V.; Yuskiv, I. D.; PishchalenkoM. А. (Regulatory Mechanisms in Biosystems, 2020)
Deinvasion, aimed at elimination of environmental exogenic stages of invasion agents and avoidance of their invasion to host organism, occupies an important place in the complex of sanitary and prophylactic activities against animal helminthosis diseases. Application of glutaraldehyde and benzalkonium chloride at vital activity and embryogenesis of Aonchotheca bovis (Schnyder, 1906) obtained from nematode female gonads was investigated with different concentration and exposures. Two test-cultures were used in the experiment. The first culture contained non-invasive eggs of A. bovis, the second contained invasive ones, obtained by the laboratory culturing of gonadic eggs until mobile larva maturing. It was established that glutaraldehyde and benzalkonium chloride mixture has a deinvasive capacity against A. bovis eggs, parasitizing on sheep. Ovocidal efficiency indexes appeared higher with use of the test culture against the non-invasive capillaria eggs’ test-culture. So, the high level of ovocidal efficiency of glutaraldehyde and benzalkonium chloride mixture against non-invasive A. bovis eggs culture was established at the concentration of 0.5% and exposure of 10–60 min (93.6–100.0%), and against the invasive A. bovis egg culture – at the concentration of 0.5% and exposure of 30 and 60 min (90.3–94.6%) and 1.0% at all exposures (100.0%). Ovocidal activity of the examined mixture was accompanied by specific morphological changes of nematode eggs structure. Destruction of the egg envelope, embryo loosening and decay and its dissolution were observed. Such changes are proved by metric indexes of width and length of capillaria eggs, envelope thickness and cap length, indicating the violation of embryogenesis of A. bovis. Thus, glutaraldehyde and benzalkonium chloride mixture of 1.0% concentration is a promising deinvasive agent suitable for effective fight against and prophylaxis of sheep-breeding nematodosis.